Who's in charge? End-users challenge graphic designers' intuition through visual verbal co-design. (28th July 2017) - Taffe, Simone
Abstract: This paper aims to understand how co-design influences the design process, by presenting a case study where graphic designers and end-users co-designed asthma information. Three co-design activities are presented, as part of a larger project, revealing insights for the next generation of graphic designers. The co-design activities built a trusting, enjoyable environment, while posing the question are designers still in charge of the process? A visual verbal game dissolved participant status barriers, a persona scenario activity uncovered the real brief and a mix and match card game suspended participant politics. The findings suggest that co-designing with end-users, challenges graphic designers' use of intuition, as new ways of categorizing asthma information material were revealed that previous design-led processes had overlooked. This study confirms the rich contribution of end-users' creativity, when designers relinquish creative control, ultimately revealing co-design as a valuable approach for graphic designers engaging in bottom-up design processes.